Analysis Of Teacher Performance In Lesson Study And Student Self-Learning In The Subject Of Basic Automotive Engineering In SMK Negeri I Palangka Raya - Debora, Debora; Supriyadi, Supriyadi; Suryanto, Ahmad Eko; Pancawati, Ratna; Nahan, Vontas Alfenny; Jaya, Harie Satiyadi; Reinaldo, Erfandi; Aridinata, Ferdi (Jurnal Ilmiah Kanderang Tingang, 2023)
This research aims to analyse teachers' performance in Lesson Study implementation and its impact on students' self-learning in Basic Automotive Engineering subject at SMK Negeri 1 Palangkla Raya. Lesson Study is a method of developing teacher professionalism that focuses on planning, observing, and reflecting on learning, while students' self-learning to learn independently. The research was conducted using qualitative methods and data were obtained through classroom observations, interviews with teachers, and questionnaires to students. The results showed that the teacher's performance in implementing lesson planning, the use of teaching materials and the effectiveness of learning is very good, only in technical skills and the application of learning strategies that are still lacking and need to be improved. Meanwhile, students' self-learning tends to be low which is inversely proportional to teachers' self-learning which tends to be high.